Electrode material for secondary batteries, secondary battery, slurry for secondary battery electrodes, and manufacturing method of electrode material for secondary batteries

The integration of a high G/D ratio carbon nanotube network with active material particles in the secondary battery electrode material addresses the limitations of existing materials by providing a bendable and high-performance energy storage solution.

JP2025068479APending Publication Date: 2025-04-28NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023178425
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-28

AI Technical Summary

Technical Problem

Existing secondary battery electrode materials lack bendability and high charge/discharge properties, limiting their application in flexible and high-performance energy storage devices.

Method used

A secondary battery electrode material comprising a network of carbon nanotubes with active material particles dispersed between the gaps, where the carbon nanotubes have a specific G/D ratio and the active material particles constitute 90% or more by weight, enabling a self-supporting film without the need for a current collector.

Benefits of technology

The electrode material achieves high mechanical strength, flexibility, and enhanced charge/discharge characteristics, allowing for the formation of free-standing films with improved cycle stability and reduced weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025068479000001_ABST
    Figure 2025068479000001_ABST
Patent Text Reader

Abstract

To provide an electrode material which is foldable and has high charge / discharge characteristics.SOLUTION: A secondary battery electrode material includes: a carbon nano-tube structure part which comprises a plurality of carbon nano-tubes and in which a network is formed by entangling the plurality of carbon nano-tubes and a plurality of clearances is formed on a plane or a cross section; and a plurality of active material particles disposed in the plurality of clearances. A concentration of the active material particles is 90 wt.% or more. In the electrode material for secondary batteries, the carbon nano-tube structure part may also be a self-supporting film.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode material for a secondary battery, a secondary battery, a slurry for a secondary battery electrode, and a method for producing an electrode material for a secondary battery. [Background technology]

[0002] Secondary batteries are widely used as power sources for electric vehicles, mobile devices, etc. Lithium-ion batteries are secondary batteries that can be charged and discharged by the movement of lithium ions in an electrolyte between a positive electrode and a negative electrode that absorb and release lithium ions. In recent years, research and development of battery materials using carbon nanotubes has been progressing (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-072279 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of one embodiment of the present invention is to provide an electrode material that is bendable and has high charge / discharge characteristics. [Means for solving the problem]

[0005] According to one embodiment of the present invention, there is provided an electrode material for a secondary battery, comprising: a carbon nanotube structure having a plurality of carbon nanotubes, the plurality of carbon nanotubes being entangled to form a network and forming a plurality of gaps in a planar or cross-sectional view; and a plurality of active material particles arranged in the plurality of gaps, wherein a concentration of the active material particles is 90% by weight or more.

[0006] In the electrode material for a secondary battery, the carbon nanotube structure may be a free-standing film.

[0007] In the above-mentioned electrode material for secondary batteries, the Raman spectrum of carbon nanotubes is 1560 to 1600 cm -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 When the maximum peak intensity within the range is D, The carbon nanotubes may have a G / D ratio of 5 or more and 120 or less.

[0008] In the secondary battery electrode material, the concentration of the carbon nanotubes may be 0.1% by weight or more and 10% by weight or less.

[0009] In the secondary battery electrode material, the concentration of the carbon nanotubes may be 0.1% by weight or more and 2.5% by weight or less, and the concentration of the active material particles may be 95% by weight or more.

[0010] In the secondary battery electrode material, the active material particles may contain any one of a nickel-manganese-cobalt alloy, a nickel-cobalt-aluminum alloy, an olivine-type lithium iron phosphate, lithium cobalt oxide, lithium titanate, silicon, silicon oxide, and graphite.

[0011] In the secondary battery electrode material, the active material particles may have a diameter of 50 nm or more and 30 μm or less.

[0012] In the electrode material for a secondary battery, the carbon nanotube structure may further include a polymer dispersant.

[0013] In the secondary battery electrode material, the carbon nanotubes may be single-walled carbon nanotubes.

[0014] In the above-mentioned electrode material for a secondary battery, the carbon nanotube structure portion may include a bundle formed of the plurality of carbon nanotubes, and the bundle may have a diameter of 5 nm or more and 100 nm or less.

[0015] According to one embodiment of the present invention, there is provided a secondary battery including the above-mentioned electrode material for a secondary battery.

[0016] According to one embodiment of the present invention, a solvent, a plurality of active material particles dispersed in the solvent, and carbon nanotubes having a peak at 1560 to 1600 cm in a Raman spectrum are provided. -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1 When the maximum peak intensity within the range is defined as D, the G / D ratio is 5 or more and 120 or less, and a plurality of carbon nanotubes are dispersed in the solvent.

[0017] In the secondary battery electrode slurry, the active material particles may contain any one of a nickel-manganese-cobalt alloy, a nickel-cobalt-aluminum alloy, an olivine-type lithium iron phosphate, lithium cobalt oxide, lithium titanate, silicon, silicon oxide, and graphite.

[0018] In the slurry for a secondary battery electrode, the active material particles may have a diameter of 50 nm or more and 30 μm or less.

[0019] The slurry for a secondary battery electrode may further include a polymer dispersant attached to the carbon nanotubes.

[0020] In the slurry for a secondary battery electrode, the carbon nanotubes may be single-walled carbon nanotubes.

[0021] In the above slurry for a secondary battery electrode, a bundle formed of the plurality of carbon nanotubes may be provided, and the bundle may have a diameter of 5 nm or more and 100 nm or less. The bundle may have an aspect ratio of 200 or more.

[0022] According to one embodiment of the present invention, the carbon nanotube has a Raman spectrum of 1560 to 1600 cm -1 The maximum peak intensity in the range of 1310 to 1350 cm is G.-1 The present invention provides a method for producing an electrode material for a secondary battery, the method including: adding a plurality of carbon nanotubes having a G / D ratio of 5 or more and 120 or less to a solvent to prepare a dispersion liquid, where D is the maximum peak intensity within the range; adding a plurality of active material particles to the dispersion liquid; and forming the dispersion liquid containing the plurality of active material particles into a substrate.

[0023] In the method for producing an electrode material for a secondary battery, the carbon nanotubes may be single-walled carbon nanotubes.

[0024] In the method for producing an electrode material for a secondary battery, the dispersion may be prepared by dissolving a polymer dispersant in the solvent and adding the carbon nanotubes to the solvent. Effect of the Invention

[0025] According to one embodiment of the present invention, it is possible to provide an electrode material that is bendable and has high charge / discharge characteristics. [Brief description of the drawings]

[0026] [Figure 1] 1 is a schematic cross-sectional view of a lithium-ion battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a positive electrode active material layer according to one embodiment of the present invention. [Diagram 3] 2 is a schematic diagram showing a part of a carbon nanotube structure according to one embodiment of the present invention; FIG. [Figure 4] 2 is a schematic diagram showing a part of a carbon nanotube structure according to one embodiment of the present invention; FIG. [Diagram 5] 1 is a histogram showing the relationship between bundle diameter and frequency in the CNT raw material used in Example 1. [Figure 6] This is an optical microscope image of a dispersion of CNTs in a solvent, 1,5-pentanediol. [Figure 7A] This is a scanning electron microscope image of the surface of a free-standing CNT film using hexylene glycol as a solvent. [Figure 7B] This is a scanning electron microscope image of the surface of a free-standing CNT film using hexylene glycol as a solvent. [Figure 8] 1 is a histogram of the diameter of CNT bundles in a free-standing CNT film using hexylene glycol as a solvent. [Figure 9] This is a scanning electron microscope image of the surface of a free-standing CNT film using 1-octanol as a solvent. [Figure 10] This is a scanning electron microscope image of the surface of a free-standing CNT film using 1,4-butanediol as a solvent. [Figure 11] 1 is a scanning electron microscope image of the surface of CNTs using 1,5-pentanediol as a solvent. [Figure 12] 1 is a histogram of CNT bundle diameters for free-standing CNT films using 1,5-pentanediol as a solvent. [Figure 13] This is a surface scanning electron microscope image of a free-standing film of Li(Ni0.33Mn0.33Co0.33)O2(NMC111) electrode composite obtained from a dispersion using hexylene glycol. [Figure 14] This is a scanning electron microscope image of the surface of a free-standing film of NMC111 electrode composite obtained from a dispersion using 1-octanol. [Figure 15] This is a surface scanning electron microscope image of a free-standing film of NMC111 electrode composite obtained from a dispersion using 1,4-butanediol. [Figure 16] This is a scanning electron microscope image of the surface of a free-standing film of NMC111 electrode composite obtained from a dispersion using 1,5-pentanediol. [Figure 17A] This is a photograph of the NMC111 electrode composite free-standing film being folded lengthwise and widthwise. [Figure 17B] This is a photograph of a free-standing film of NMC111 electrode composite with creases made lengthwise and widthwise. [Figure 17C] This is a photograph of a free-standing film of NMC111 electrode composite that was folded lengthwise and widthwise and then pulled in the left and right directions. [Figure 18]1 is a scanning electron microscope image of the surface of a free-standing film of an electrode composite with a CNT concentration of 0.50% by weight. [Figure 19] This is a scanning electron microscope image of the surface of a free-standing film of an electrode composite with a CNT concentration of 4.5% by weight. [Figure 20] This is a cross-sectional scanning electron microscope image (magnification 3000 times) of a free-standing film of an electrode composite with a CNT concentration of 0.98% by weight. [Figure 21] This is a cross-sectional scanning electron microscope image (magnification 50,000 times) of a free-standing film of an electrode composite with a CNT concentration of 0.98% by weight. [Figure 22] 1 shows the results of thermogravimetric analysis of a free-standing film of an electrode composite material. [Diagram 23] This is a surface scanning electron microscope image of an electrode composite film containing Li(Ni0.5Mn0.3Co0.2)O2 (NMC532) as active material particles. [Figure 24] This is a surface scanning electron microscope image of an electrode composite film containing Li(Ni0.8Mn0.1Co0.1)O2 (NMC811) as active material particles. [Diagram 25] This is a surface scanning electron microscope image of an electrode composite film containing single crystal Li(Ni0.9Mn0.05Co0.05)O2 (single NMC91) as the active material particle. [Figure 26] This is a surface scanning electron microscope image of an electrode composite film containing Li(Ni0.8Co0.1Al0.1)O2 (NCA811) as active material particles. [Figure 27] 1 is a surface scanning electron microscope image of an electrode composite film containing lithium iron phosphate LiFePO4 (LFP) as active material particles. [Figure 28] 1 is a surface scanning electron microscope image of an electrode mixture film containing SiO as active material particles. [Figure 29] 1 is a surface scanning electron microscope image of an electrode mixture film containing Si as active material particles. [Diagram 30] 1 is a surface scanning electron microscope image of an electrode composite film containing Li2TiO3 (LTO) as active material particles. [Diagram 31] 1 is a surface scanning electron microscope image of an electrode mixture film containing graphite as active material particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Hereinafter, the electrode material for secondary batteries, the secondary battery, the slurry for secondary battery electrodes, and the method for manufacturing the electrode material for secondary batteries according to the present invention will be described with reference to the drawings. Note that the electrode material for secondary batteries, the secondary battery, the slurry for secondary battery electrodes, and the method for manufacturing the electrode material for secondary batteries according to the present invention are not to be interpreted as being limited to the description of the embodiments and examples shown below. Note that in the drawings referred to in the present embodiment and the examples described below, the same parts or parts having similar functions are given the same reference numerals, and repeated explanations thereof will be omitted.

[0028] For example, in the case of conventional lithium-ion batteries, a current collector is essential, making it difficult to realize a foldable, wearable battery. In addition, because conventional current collectors are made of metal foil, there is a limit to how light the lithium-ion battery can be. If an electrode material were to be manufactured without using a current collector, a free-standing film could be formed by increasing the concentration of carbon nanotubes (CNTs) or carbon fibers, but the concentration of the active material would be low, making it impossible to improve the strength or charge / discharge characteristics of the film itself.

[0029] Therefore, the present inventors conducted extensive research and found that by arranging an active material inside a carbon nanotube, it is possible to make the carbon nanotube bendable and improve the charge / discharge characteristics.

[0030] (1. Structure of secondary battery) 1 is a schematic cross-sectional view of a secondary battery. The secondary battery 10 of this embodiment includes a positive electrode 110, a negative electrode 120, a separator 130 disposed between the positive electrode 110 and the negative electrode 120, an exterior body 140, and an electrolyte 150 containing a lithium salt. In the secondary battery 10, the positive electrode 110 and the negative electrode 120 are insulated and sealed.

[0031] The positive electrode 110 has a positive electrode terminal 111 and a positive electrode active material layer 113 connected to the positive electrode terminal 111. The positive electrode terminal 111 has a sheet shape. In this example, aluminum foil is used for the positive electrode terminal 111. The positive electrode active material layer 113 is a porous layer and is a layer containing a positive electrode active material.

[0032] The thickness of the positive electrode active material layer 113 is not particularly limited, but is preferably 1 μm or more and 100 μm or less. By making the thickness of the positive electrode active material layer 113 1 μm or more, the amount of the positive electrode active material contained in the positive electrode active material layer 113 can be increased, and the capacity of the secondary battery can be increased. In addition, the positive electrode active material layer 113 can be formed by a coating process. The positive electrode active material layer 113 will be described in detail below.

[0033] The negative electrode 120 has a negative electrode terminal 121 partially exposed to the outside, and a negative electrode active material layer 123 connected to the negative electrode terminal 121. The negative electrode terminal 121 has a sheet shape. In this example, the negative electrode terminal 121 is made of copper foil. The negative electrode active material layer 123 is made of graphite. In this embodiment, the positive electrode active material layer 113 and the negative electrode active material layer 123 have basically the same configuration except for the material of the active material. Therefore, in this embodiment, the following description will focus mainly on the positive electrode active material layer 113.

[0034] The separator 130 may be made of an insulating material such as cellulose (paper) or porous polypropylene or polyethylene.

[0035] The exterior body 140 is provided so as to encase the positive electrode 110, the negative electrode 120, and the separator 130. The exterior body 140 is flexible. An insulating material, in particular a resin material such as a polyamide resin, a polyimide resin, or an acrylic resin, is used for the exterior body 140. In this example, a polyimide resin is used.

[0036] A material having carrier ions is used for the electrolyte 150. Representative examples of the electrolyte include LiClO4, LiAsF6, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, and Li2B 10 Cl10 , Li2B 12 Cl 12 Lithium salts include LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), and LiN(C2F5SO2)2.

[0037] In addition, when the carrier ion is an alkali metal ion other than a lithium ion, an alkaline earth metal ion, a beryllium ion, or a magnesium ion, an alkali metal (e.g., sodium, potassium, etc.), an alkaline earth metal (e.g., calcium, strontium, barium, etc.), beryllium, or magnesium may be used as the electrolyte in place of lithium in the above-mentioned lithium salt.

[0038] In this example, the electrolyte 150 is a liquid electrolyte (electrolyte). A material capable of transporting carrier ions is used as a solvent for the electrolyte. An aprotic organic solvent is preferable as a solvent for the electrolyte. Representative examples of the aprotic organic solvent include ethylene carbonate (EC), propylene carbonate, butylene carbonate, chloroethylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone, γ-valerolactone, methyl formate, methyl acetate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, dimethoxyethane, tetrahydrofuran, sulfolane, and sultone, and one or more of these can be used. In addition, by using a gelled polymer material as a solvent for the electrolyte, safety against leakage and the like is improved. In addition, it is possible to make the secondary battery thinner and lighter.Typical examples of polymeric materials that can be gelled include silicone gel, acrylic gel, acrylonitrile gel, polyethylene oxide, polypropylene oxide, and fluorine-based polymers.

[0039] (2. Configuration of Positive Electrode Active Material Layer) The positive electrode active material layer will be described below. Fig. 2 is a cross-sectional schematic diagram of the positive electrode active material layer 113. The positive electrode active material layer 113 includes a plurality of positive electrode active material particles 1131 and a carbon nanotube structure portion 1133. The positive electrode active material layer 113 can also be called an electrode material (or an electrode mixture) for a secondary battery.

[0040] (2-1. Positive electrode active material particles) The positive electrode active material particles 1131 are directly involved in the transfer of electrons accompanying charge transfer in the positive electrode. In this example, a nickel manganese cobalt alloy (more specifically, NMC111) is used for the positive electrode active material particles 1131. The particle diameter of the positive electrode active material particles 1131 is not particularly limited, but is preferably 50 nm or more and 30 μm or less in terms of the relationship with the structure (length) of the carbon nanotube structure portion 1133 (e.g., coverage rate) and the charge / discharge characteristics (cycle characteristics).

[0041] (2-2. Carbon nanotube structure) 3 is a schematic plan view of the carbon nanotube structure 1133. As shown in FIG. 3, the carbon nanotube structure 1133 includes a carbon nanotube (also referred to as CNT) 11331. In this example, the carbon nanotube has high crystallinity. The crystallinity is expressed by the G / D ratio. Specifically, the G / D ratio of the CNT is expressed by the G / D ratio at 1590 cm in a Raman spectrum obtained by Raman spectroscopy using light with an excitation wavelength of 532 nm. -1 Near (1560~1600cm -1 The peak of the G-band due to the graphite structure observed at 1320 cm -1 Nearby (1310~1350cm -1 The G / D ratio is the ratio of the peak of the D-band derived from defects in the graphite structure observed in the range of 100 to 120. A high G / D ratio of a CNT indicates that damage or defects in the CNT are reduced. The average G / D ratio of the CNT is the average value of at least five measured points. In this embodiment, it is desirable that the carbon nanotube structure 1133 is composed of CNTs with a G / D ratio of 5 or more, preferably 10 to 120.

[0042] The carbon nanotube structure 1133 is composed of a single CNT 11331 or a bundle 11333 which is a bundle-shaped structure formed by agglomeration of the CNTs 11331. The CNTs 11331 have a diameter of 1 nm or more and 5 nm or less. The CNTs 11331 may be single-walled CNTs (SWCNTs) or multi-walled CNTs (MWCNTs) (specifically, double-walled CNTs (DWCNTs)). The diameter of the bundles 11333 is desirably 10 nm or more and 100 nm or less. The length of the CNTs 11331 (or the bundles 11333) may be 1 μm or more.

[0043] In the bundle 11333, the CNTs 11331 are locally aligned, but may have a structure in which the CNTs 11331 are partially separated from each other. Also, the bundle 11333 has one or more of a portion where the CNTs 11331 contact each other (contact portion 11335a), a portion where the CNT bundles 11333 contact each other (contact portion 11335b), and a portion where the CNTs 11331 and the CNT bundles 11333 contact each other (contact portion 11335c).

[0044] In this embodiment, the carbon nanotube structure 1133 forms a network in which CNTs are entangled in the in-plane direction. In this case, the network structure (network structure) is one that looks like a mesh in a plan view, and the CNTs are not chemically bonded to each other, but are bonded by van der Waals forces (intermolecular forces). As shown in FIG. 2, the positive electrode active material layer 113 has a thickness, so that when the CNTs form a network in the carbon nanotube structure 1133, a plurality of CNTs are entangled in the thickness direction (cross-sectional direction) to form a three-dimensional network structure. Therefore, it can be said that the carbon nanotube structure 1133 has a plurality of gaps 1135 in the in-plane direction and the cross-sectional direction. The size of the gaps 1135 in the cross-sectional (film thickness) direction is preferably 10 nm or more and 10 μm or less. The size of the gaps 1135 in the in-plane direction is preferably 1 μm or more and 500 μm or less. With the above-mentioned configuration, the carbon nanotube structure 1133 has long bundles and uniformly distributed bundle diameters, and thus has high mechanical strength to the extent that it can form a free-standing film. Even if it is bent (stress is applied), each CNT can maintain its network and distribute stress uniformly, so that it can maintain its shape.

[0045] (2-3. Relationship between positive electrode active material particles and carbon nanotube structure) The positive electrode active material particles 1131 are disposed in the plurality of gaps 1135 described above. The positive electrode active material particles 1131 are in partial contact with the CNTs. Adjacent positive electrode active material particles 1131 (in this example, the positive electrode active material particle 1131-1 and the positive electrode active material particle 1131-2) are in partial contact with each other. In one embodiment of the present invention, van der Waals forces (intermolecular forces) are generated between the positive electrode active material particles 1131 and the CNTs, and the carbon nanotube structure portion 1133 has a three-dimensional network structure. These prevent the positive electrode active material particles 1131 from leaking out of the carbon nanotube structure portion 1133.

[0046] In addition, in the network of the carbon nanotube structure 1133, electrical connection between the CNTs 11331 and 11331 is provided at the contact portion 11335a, electrical connection between the bundles 11333 and 11333 at the contact portion 11335b, and electrical connection between the CNTs 11331 and the bundles 11333 of CNTs at the contact portion 11335c. At this time, the carbon nanotube structure 1133 comes into contact with the positive electrode active material particles 1131, so that electrons generated by the electrochemical reaction in the positive electrode active material particles 1131 can be efficiently transmitted to the entire network of the carbon nanotube structure 1133. The carbon nanotube structure 1133 can function as a conductive assistant.

[0047] Furthermore, in one embodiment of the present invention, by having the above-mentioned configuration, it is not necessary to use a binder, and the positive electrode active material particles can be disposed instead of the binder.

[0048] In this embodiment, the concentration of CNT is 0.1% by weight or more and 10% by weight or less with respect to the weight of the positive electrode active material layer 113, and the concentration of the active material particles is 90% by weight or more with respect to the weight of the positive electrode active material layer 113. More preferably, the concentration of CNT is 0.1% by weight or more and 5% by weight or less with respect to the weight of the positive electrode active material layer 113, and the concentration of the active material particles is desirably 95% by weight or more with respect to the weight of the positive electrode active material layer 113. This makes it possible to increase the ratio of the active material particles in the positive electrode active material layer 113, and to increase the charge / discharge capacity. Furthermore, in one embodiment of the present invention, even if the positive electrode active material particles shrink or expand during charge / discharge, the carbon nanotube structure portion 1133 can maintain its structure as described above, and the cycle characteristics can be improved.

[0049] As described above, by using one embodiment of the present invention, a bendable positive electrode material having high charge / discharge characteristics can be provided. In addition, in this embodiment, since the positive electrode active material layer is a self-supporting film, a current collector is not required. This can reduce the weight of the battery.

[0050] In one embodiment of the present invention, the carbon nanotube structure may have a different configuration from the above-mentioned carbon nanotube structure. FIG. 4 is a schematic diagram showing a carbon nanotube structure 1133A according to one embodiment of the present invention. In one embodiment of the present invention, the carbon nanotube structure 1133A may include a polymer dispersant 11337 together with the CNTs 11331. As the polymer dispersant, polyacrylic acid (hereinafter also referred to as "PAA"), polymethacrylic acid, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinylpyrrolidone, or any combination thereof is used. In this example, polyacrylic acid having an average molecular weight of 500 or more and 250,000 or less is used as the polymer dispersant 11337. In addition, the weight ratio of CNTs:polyacrylic acid may be from 1:0.5 to 1:5.

[0051] The carbon nanotube structure 1133 includes a single CNT 11331 or a bundle 11333 which is a bundle-shaped structure formed by agglomeration of CNTs 11331. The polymer dispersant 11337 includes a portion where the polymer dispersant 11337 is attached to a single CNT 11331 or a CNT bundle 11333 and a portion where the CNT 11331 is exposed. The polymer dispersant 11337 is attached so as to surround the periphery of the single CNT 11331 or the CNT bundle 11333 by van der Waals forces.

[0052] The carbon nanotube structure 1133 includes a network of polymer dispersant 11337 and CNTs 11331, and while the polymer dispersant 11337 is disposed around the CNTs 11331, contact between the CNTs 11331 is also ensured. Therefore, in the carbon nanotube structure 1133, the electrical connection between the CNTs 11331 and CNTs 11331, the electrical connection between the bundles 11333 and bundles 11333, and the electrical connection between the CNTs 11331 and CNT bundles 11333 are not hindered by the polymer dispersant 11337. Therefore, the carbon nanotube structure 1133 improves the electrical connection in the CNT network and has excellent electrical performance.

[0053] (3. Method for producing positive electrode active material layer) A method for producing the positive electrode active material layer (positive electrode material, electrode mixture) will be described in detail below.

[0054] (3-1. Preparation of CNT dispersion) The CNT dispersion liquid is described below: In this embodiment, the CNT dispersion liquid forms a carbon nanotube structure portion, and contains CNTs and a solvent.

[0055] (3-1-1. Preparation of CNTs) The CNTs are formed by the eDIPS method. The CNTs have a diameter of 0.5 nm or more and 2.5 nm or less. The CNTs are preferably single-walled CNTs. The G / D ratio of the CNTs is preferably 5 or more, more preferably 10 or more and 120 or less.

[0056] (3-1-2. Preparation of solvent) The solvent may be any solvent capable of dispersing CNT, including water and organic solvents. In one embodiment of the present invention, since the CNT dispersion contains positive electrode active material particles as described later, it is preferable to select the solvent and the polymer dispersant described later in consideration of the viscosity of the dispersion. This is because the stability of the dispersion of the positive electrode active material particles and CNT in the dispersion and the film formability (indicating the uniformity of the film thickness, the uniformity of the composition in the film, the adhesiveness to the substrate, etc.) are related to the viscosity. The viscosity of the dispersion is preferably in the range of 10 to 100 mPa·s. Similarly, the solvent and the polymer dispersant may be selected in consideration of the boiling point of the dispersion.

[0057] Examples of the single solvent used in one embodiment of the present invention include, but are not limited to, 1-propanol, 2-propanol, 1-butanol, 1,4-butanediol, 1-octanol, 1,5-pentanediol, ethylene glycol, hexylene glycol, etc. Examples of the mixed solvent include, but are not limited to, a combination of alcohol-based solvents such as a mixed solvent of ethanol and 2-propanol (0.5:9.5), a mixed solvent of ethanol and 2-butanol (1:9), a mixed solvent of 1-propanol and 2-butanol (0.5:9.5 to 1:9), a mixed solvent of 1-propanol and iso-butanol (0.5:9.5 to 2:8), and a mixed solvent of 1-propanol and 1-pentanol (0.5:9.5 to 2:8). Furthermore, the combination of the alcoholic solvent and the non-alcoholic solvent can be selected from, for example, a mixed solvent of 1-propanol and 1,4-dioxane (5:5 to 9:1), a mixed solvent of 1-propanol and methyl isobutyl ketone (hereinafter also referred to as MIBK) (5:5 to 9:1), and the like, but is not limited thereto.

[0058] In one embodiment of the present invention, the polymer dispersant may be, but is not limited to, at least one selected from the group consisting of polymeric carboxylic acids such as polyacrylic acid and polymethacrylic acid, and polymers such as poly(p-styrenesulfonic acid), carboxymethylcellulose, hydroxypropylcellulose, and polyvinylpyrrolidone. In the CNT dispersion, a small amount of these polymers can uniformly disperse CNTs, and can increase the concentration of positive electrode active material particles in the positive electrode active material layer.

[0059] In one embodiment of the present invention, the weight average molecular weight of the polymer dispersant is from 500 to 250,000, and preferably from 1,800 to 25,000. The average number of repeating units of polyacrylic acid is from 8 to 3,500, and preferably from 25 to 350.

[0060] The Hansen solubility parameter (hereinafter also referred to as HSP) of the solvent may be appropriately set. In this embodiment, the dD value of the solvent is 13.5 MPa. 0.5 More than 17.5MPa 0.5 Below, dP value is 3MPa 0.5 More than 8MPa 0.5 Below, dH value is 9MPa 0.5 More than 18MPa 0.5 Here, the dD value indicates the energy due to intermolecular dispersion forces, the dP value indicates the energy due to intermolecular dipole interactions, and dH indicates the energy due to intermolecular hydrogen bonds.

[0061] These three parameters can be plotted on the coordinates of a three-dimensional space (Hansen space). When the HSP of the CNT and the HSP of the solvent are plotted in Hansen space, the closer the distance between the two points, the easier it is for the CNT to disperse in the solvent. The distance Ra between the HSP of the CNT and the HSP of the solvent is calculated by the following formula:

number

[0062] The defibration of CNTs can be controlled by the distance Ra of the HSP of the solvent. It is possible to maintain the asbestos ratio of the CNT bundle and control the diameter and length of the CNT bundle depending on the size and shape of the active material. In one embodiment of the present invention, thinner CNT bundles are required, and it is desirable that the distance Ra of the HSP of the solvent is 10 or less.

[0063] The solvent is preferably an organic solvent for the purpose of removing it from the CNT dispersion liquid in the manufacturing process of the positive electrode active material layer, and is not particularly limited as long as it has the above HSP and Ra ranges. The second solvent may be one type of solvent having HSP and Ra in the above HSP and Ra ranges, or two types of solvents may be mixed to prepare a mixed solvent having HSP and Ra in the above HSP and Ra ranges. Furthermore, three or more types of solvents may be mixed to prepare a mixed solvent having HSP and Ra in the above HSP and Ra ranges.

[0064] For example, when preparing a mixed solvent using two types of solvents, by adjusting the mixing ratio of the first solvent A and the second solvent B, a mixed solvent having HSP and Ra within the above-mentioned HSP and Ra ranges can be prepared.

[0065] (3-1-3. Pre-dispersion process) Next, in the pre-dispersion step, a polymer dispersant is dissolved in the above-mentioned solvent, CNT powder is added, and the mixture is vigorously stirred with a magnetic stirrer or the like for several tens of minutes to a day.

[0066] (3-1-4. Main dispersion process) Next, in the main dispersion process, the pre-dispersed liquid is used to further disperse the CNTs using an ultrasonic homogenizer, ultrasonic bath, mixer, jet mill high-pressure dispersion, etc., to obtain a CNT dispersion in which the CNTs do not easily aggregate or settle.

[0067] In this dispersion process, when an ultrasonic homogenizer is used, CNTs can be strongly dispersed, but if it takes too long, there is a risk of damaging the CNTs and the polymer dispersant. The G / D ratio of the CNT raw material formed by the eDIPS method is 100 or more, but when dispersed with an ultrasonic homogenizer, the G / D ratio can decrease to 5. In addition, when a solution containing a polymer dispersant is heated during the preparation of a CNT dispersion, it is presumed that the polymer dispersant self-aggregates in the CNT dispersion, reducing the area of ​​contact between the polymer dispersant and the CNTs. In general, when dispersing CNTs with an ultrasonic homogenizer, the solvent molecules and the polymer dispersant are vibrated, generating high heat locally, which causes the polymer dispersant to aggregate violently. This also prevents contact between the CNTs. In addition, the dispersion energy given to the CNTs is not uniform, and the bundle distribution is also not uniform.

[0068] For this reason, it is effective to minimize the processing time with the ultrasonic homogenizer or to irradiate the pre-dispersed liquid with ultrasonic waves while cooling it. For example, by performing pre-dispersion for about 11 hours, a uniform dispersion can be obtained even if the time of ultrasonic homogenizer irradiation in the main dispersion is shortened, and damage to the CNTs and polymer dispersant caused by ultrasonic homogenizer irradiation can be minimized. As a result, the change in the G / D ratio of the CNTs before and after dispersion can be suppressed. In addition, by using a solvent suitable for the Hansen solubility parameter of CNTs, a highly dispersible and stable dispersion can be obtained even with a mild dispersion method such as pre-dispersion, and both the quality and productivity of the dispersion can be achieved.

[0069] (3-1-5. Addition of Positive Electrode Active Material Particles) Next, positive electrode active material particles are added to the CNT dispersion liquid. In this example, a nickel-cobalt-manganese alloy (more specifically, NMC111) is added. The size of the positive electrode active material particles is preferably 50 nm or more and 30 μm or less. In this way, a dispersion liquid (also called a slurry) is prepared. A composition of the positive electrode active material layer is formed in the dispersion liquid.

[0070] (3-2. Coating of Positive Electrode Active Material Layer Composition) Next, the dispersion liquid is applied to the surface of a substrate (a resin-based material, in this example, a polyimide resin). At this time, the application method may be a spin coating method, a spray coating method, or a bar coating method. Next, the applied composition is dried. The heating temperature during drying may be, for example, 100°C. In this manner, a positive electrode active material layer can be formed. The formed positive electrode active material layer may be peeled off from the substrate (may be a free-standing film) or may be disposed on the substrate as it is.

[0071] By using this embodiment, the thickness and length of the bundle can be adjusted by controlling the manufacturing method of the positive electrode active material layer 113, and an optimal positive electrode active material layer can be manufactured according to the type (size) of the active material and the type of the battery. This makes it possible to increase the concentration of the active material, to make the layer bendable, and to improve the battery characteristics.

[0072] <Modification> The present disclosure is not limited to the above-described embodiment, and includes various other modified examples. For example, the above-described embodiment has been described in detail to clearly explain the present disclosure, and is not necessarily limited to those having all the configurations described. In addition, a part of the configuration of one embodiment may be replaced with the configuration of another embodiment, and it is also possible to add the configuration of another embodiment to the configuration of one embodiment. In addition, it is possible to add, delete, or replace other configurations with respect to a part of the configuration of each embodiment. Some modified examples will be described below. Note that an example of modifying one embodiment can also be applied as an example of modifying another embodiment.

[0073] In the embodiment of the present invention, the positive electrode active material particles 1131 are made of nickel manganese cobalt alloy (more specifically, NMC111), but the present invention is not limited thereto. The positive electrode active material particles 1131 may be made of nickel manganese cobalt alloy with a different compounding ratio from NMC111 (e.g., NMC532, NMC811, or NMC91 alone), or may be made of at least one of nickel cobalt aluminum alloy (NCA), olivine-type lithium iron phosphate (LFP), and lithium cobalt oxide.

[0074] In addition, in the embodiment of the present invention, graphite is used as the negative electrode active material in the negative electrode active material layer 123, but the present invention is not limited thereto. For example, silicon, silicon oxide, or lithium titanate (LTO) may be used as the negative electrode active material.

[0075] In addition, in the embodiment of the present invention, a lithium ion battery is shown as an example of a secondary battery, but the present invention is not limited thereto. For example, other secondary batteries such as a sodium ion battery, a sodium sulfur battery, and a lithium ion polymer battery can be applied. In addition, an all-solid-state battery using a solid electrolyte such as ceramic, polymer, or cellulose as an electrolyte can be applied.

[0076] In addition, although an example of the CNT according to an embodiment of the present invention uses CNTs produced by the improved direct injection pyrolysis synthesis (eDIPS) method, CNTs produced by other methods may be used. For example, single-walled CNTs such as super growth method or TUBALL, multi-walled CNTs such as vapor grown carbon fiber (VGCF) or JEIO may be used.

[0077] In the embodiment of the present invention, an example in which one positive electrode active material layer 113, one negative electrode active material layer 123, and one separator 130 are provided has been shown, but the present invention is not limited thereto. For example, a plurality of positive electrode active material layers 113, a plurality of negative electrode active material layers 123, and a plurality of separators 130 may be provided. This can further improve the battery capacity. EXAMPLES

[0078] Next, the present invention will be described in more detail based on examples. Note that the following explanation is for the purpose of facilitating understanding of the present invention, and is not intended to be limiting. In other words, all modifications, embodiments, and other examples based on the technical concept of the present invention are included in the present invention.

[0079] In the following examples, we used single-walled CNTs (eDIPS) synthesized by an improved direct injection pyrolysis synthesis method from Meijo Nano Carbon Co., Ltd. In addition, we used a reagent manufactured by Wako Pure Chemical Industries, Ltd. for polyacrylic acid (PAA, weight average molecular weight 5,000).

[0080] (Measuring method / equipment) First, the measurement methods and devices used in the examples will be described. [Scanning electron microscope] For structural observation using a scanning electron microscope, S4800 (Hitachi High-Technologies Corporation) was used. [Raman spectroscopy] Raman spectroscopy was performed using XploRA (manufactured by Horiba Manufacturing Co., Ltd.). [Thermogravimetric analysis] Thermogravimetric analysis of the electrode mixture was performed using a TGA Q5000 IR (manufactured by TA Instruments), and the concentration of the active material was calculated. [Tensile strength] The tensile strength of the free-standing film was measured using a micro strength evaluation tester MST-I (manufactured by Shimadzu Corporation). [Surface resistance] The surface resistivity of the CNT conductive film was measured at room temperature in the atmosphere using a four-probe resistivity measuring device (Loresta, manufactured by Mitsubishi Chemical Corporation). [Battery charge / discharge performance] The battery charge / discharge performance was evaluated using a VMP3 (Bio-Logic) electrochemical measurement system.

[0081] (Example 1. Evaluation of free-standing CNT electrode film) (1-1. Manufacturing of self-supporting CNT electrode films) In Example 1, CNTs, solvents, and dispersants were investigated to prepare a free-standing electrode film with excellent flexibility and mechanical strength. Figure 5 is a histogram showing the relationship between bundle diameter and frequency in the CNT raw material used in Example 1. The frequency was calculated from the number of CNT units in the bundle. The distribution range was calculated from the FWHM of the Gaussian fitting curve. The bundle diameter in the CNT raw material was 167 nm ± 90 nm.

[0082] 0.1 g of PAA (weight average molecular weight 5,000) was dissolved in 100 g of hexylene glycol (condition 1), 1-octanol (condition 2), and 1,4-butanediol (condition 3), and then 0.1 g of CNT was added and mixed. Also, 0.1 g of CNT was added to 100 g of 1,5-pentanediol without dissolving PAA and mixed (condition 4). Table 1 shows the Hansen solubility parameters of each solvent. [Table 1]

[0083] The resulting mixture was further stirred at a rotation speed of 15,000 rpm for 30 minutes to obtain a 0.1 wt% CNT dispersion. The resulting dispersion was formed into a film by the doctor blade method, dried at 100°C for about 2 hours, and then peeled off from the substrate to obtain a free-standing film. Figure 6 shows an optical microscope image (observation magnification: 500x) of a dispersion in which CNTs are dispersed in 1,5-pentanediol, dropped onto a glass plate, sandwiched between another glass plate, and the dispersion thinly spread and observed. In Figure 6, the length of the CNT bundle was 50 μm or more, the diameter (average value) of the CNT bundle was 63 nm, and the aspect ratio was over 800.

[0084] (1-2. Characterization of free-standing CNT electrode films) The bundle and network structures of CNTs in the free-standing films were evaluated by surface observation with a scanning electron microscope (SEM) and Raman spectroscopy. The surface resistivity of the free-standing CNT films was evaluated using a four-probe resistivity measuring device manufactured by Loresta.

[0085] FIG. 7A is a surface scanning electron microscope image (magnification: 10,000 times) of a CNT freestanding film using hexylene glycol as a solvent (condition 1). FIG. 7B is a surface scanning electron microscope image (magnification: 50,000 times) of a CNT freestanding film using hexylene glycol as a solvent. FIG. 8 is a histogram of the diameter of the CNT bundle in the CNT freestanding film using hexylene glycol as a solvent (condition 1). FIG. 9 is a surface scanning electron microscope image (magnification: 50,000 times) of a CNT freestanding film using 1-octanol as a solvent (condition 2). FIG. 10 is a surface scanning electron microscope image (magnification: 50,000 times) of a CNT freestanding film using 1,4-butanediol as a solvent (condition 3). FIG. 11 is a surface scanning electron microscope image (magnification: 50,000 times) of a CNT freestanding film using 1,5-pentanediol as a solvent (condition 4). FIG. 12 is a histogram of CNT bundle diameters of a CNT freestanding film (condition 4) using 1,5-pentanediol as a solvent. Table 2 shows the characterization results showing the average size, G / D ratio, and resistivity of the CNT bundles. [Table 2]

[0086] As shown in Figures 7A, 7B, 8 and Table 1, the bundles of CNTs dispersed in the dispersant PAA and the solvent hexylene glycol were thin and uniformly distributed (12 ± 5 nm), and it was confirmed that they were uniformly dispersed. In addition, the G / D ratio of the CNT film dispersed in hexylene glycol was 85, and it showed high crystallinity and high conductivity (3500 S / cm). In other words, it was found that there was very little damage to the CNTs under the conditions of the dispersion process shown in this example.

[0087] It was also found that the CNT freestanding film dispersed in hexylene glycol and peeled off from the substrate did not break even when folded 10 times with a radius of curvature of 5 mm. It was also found that the CNT freestanding film could be restored to its original shape by folding the folded part and then stretching it. The CNT freestanding film is lighter and more flexible than the conventional metal foil current collector, and has a strength that does not break even when folded. It was also found that the above-mentioned CNT freestanding film has sufficient conductivity as a current collector. In other words, it was confirmed that the use of the present embodiment does not necessarily require the use of a current collector. It was also found that a freestanding film was produced even with a CNT dispersion produced using another solvent or without a dispersant, and that it had sufficient strength and conductivity.

[0088] In addition, it was confirmed that the average bundle diameter differed depending on the solvent and dispersant used, as shown in Figures 9, 10, and 11. This indicates that the dispersibility of CNTs differs depending on the solvent and dispersant, and is considered to be influenced by the Hansen solubility parameter of CNTs.

[0089] On the other hand, as shown in FIG. 11, FIG. 12 and Table 1, in the case of CNT bundles dispersed in the solvent 1,5-pentanediol without using PAA, the bundle diameter was larger than that in the case of using a dispersant, but the distribution was uniform (63±14 nm), and it was confirmed that the bundles were uniformly dispersed. In addition, the G / D ratio of the CNT film dispersed in 1,5-pentanediol was 80, and it similarly showed high crystallinity and high conductivity (2000 S / cm). In other words, it was found that by using a mild stirring dispersion method as in this example, a very uniform bundle was formed, and it had a high G / D ratio and a length of 2 μm or more. It is believed that the network structure constructed by the highly crystalline and long uniform CNT bundles is the cause of the formation of a strong free-standing film. Under the condition where 1,5-pentanediol was used as the solvent, it was confirmed that a free-standing film can be formed by obtaining a longer uniform CNT bundle even if the CNT bundles are not finely defibrated because a dispersant is not used.

[0090] (Example 2. Evaluation of the effect of CNT dispersion state on the mixed structure of electrode active material and CNT) In this example, the effect of the CNT dispersion state on the mixed structure of the electrode active material and CNT was examined.

[0091] (2-1. Preparation of electrode composite free-standing film) The four types of dispersion liquids prepared in Example 1 were each used in an amount of 10 g to prepare a ternary positive electrode material Li(Ni 0.33 Mn 0.33 Co 0.33 0.4 g of O2 (NMC111) was added and mixed in a mixer to obtain a positive electrode slurry of NMC111.

[0092] The obtained slurry was then applied to a stainless steel foil by a doctor blade method, and the solvent was dried at 100°C for about 2 hours to form an NMC111 electrode composite layer with a CNT concentration of 2.4% by weight. The electrode composite layer was then peeled off from the stainless steel foil to obtain a free-standing NMC111 electrode composite film.

[0093] (2-2. Structural evaluation of electrode composite free-standing film) FIG. 13 is a surface scanning electron microscope image of the NMC111 electrode composite free-standing film obtained from a dispersion using hexylene glycol. FIG. 14 is a surface scanning electron microscope image of the NMC111 electrode composite free-standing film obtained from a dispersion using 1-octanol. FIG. 15 is a surface scanning electron microscope image of the NMC111 electrode composite free-standing film obtained from a dispersion using 1,4-butanediol. FIG. 16 is a surface scanning electron microscope image of the NMC111 electrode composite free-standing film obtained from a dispersion using 1,5-pentanediol. As shown in FIG. 13 to FIG. 16, NMC111 particles adhering to the CNT network structure were observed. FIG. 17A is a photograph of the NMC111 electrode composite free-standing film being folded lengthwise and widthwise. FIG. 17B is a photograph of the NMC111 electrode composite free-standing film with creases after folding. Fig. 17C is a photograph of the NMC111 electrode composite free-standing film folded lengthwise and widthwise, and then pulled in the left-right direction. As shown in Figs. 17A to 17C, it was confirmed that the NMC111 electrode composite free-standing film was not damaged even when subjected to impact such as folding or pulling. This suggests that the CNT network structure observed in Example 1 was maintained, and therefore the electrode composite layer also had a film strength sufficient to be free-standing.

[0094] (Example 3. Evaluation of the effect of CNT concentration on the mixed structure of electrode active material and CNT) In this example, the effect of CNT concentration on the mixed structure of the electrode active material and CNT was examined. The CNT dispersion was prepared using the hexylene glycol solvent of Example 1. 2 g, 1 g, 0.2 g, and 0.1 g of the ternary positive electrode material NMC111 were added to 10 g of the CNT dispersion, and then mixed with a mixer to obtain a positive electrode slurry of NMC111.

[0095] The obtained slurry was then applied to a stainless steel foil by a doctor blade method, and the solvent was dried at 100°C for about 2 hours to form an NMC111 electrode composite layer with a CNT concentration of 0.50, 1.0, 4.5, or 8.3% by weight. The electrode composite layer was then peeled off from the stainless steel foil to obtain a free-standing NMC111 electrode composite film.

[0096] (3-2. Structural evaluation of electrode composite free-standing film) Figure 18 is a surface scanning electron microscope image of a free-standing electrode composite film with a CNT concentration of 0.50 wt%. Figure 19 is a surface scanning electron microscope image of a free-standing electrode composite film with a CNT concentration of 4.5 wt%. As shown in Figures 18 and 19, NMC111 particles were observed adhering to the dense network structure of CNT. It was also confirmed that the area of ​​the dense network structure of CNT increased as the CNT concentration increased.

[0097] FIG. 20 is a cross-sectional scanning electron microscope image (magnification 3000 times) of an electrode composite free-standing film with a CNT concentration of 0.98% by weight. FIG. 21 is a cross-sectional scanning electron microscope image (magnification 50000 times) of an electrode composite free-standing film with a CNT concentration of 0.98% by weight. It was observed that multiple layers (CNT continuous layers) of CNTs with a thickness of about 100 to 200 nm in the film thickness direction were formed, and NMC111 particles were deposited (disposed) in the gaps between the CNT continuous layers. The CNT continuous layers, which are characterized by a dense network structure, spread in the electrode composite layer, and not only make the electrode composite film self-supporting even with a low CNT concentration, but also enable efficient electrical conduction.

[0098] Table 3 shows the evaluation results showing the relationship between the CNT concentration and the tensile strength and strain. [Table 3]

[0099] The tensile strength of the electrode composite free-standing film was evaluated, as shown in Table 3. It was found that the film was able to stand on its own even with a CNT concentration of 0.50% by weight, and had sufficient tensile strength. It also had a strain of 1% or more, indicating that the free-standing film had sufficient elongation to bend. It was also found that the tensile strength of the electrode composite free-standing film improved significantly as the CNT concentration increased.

[0100] (Example 4. Evaluation of the effect of dispersants on electrode composite free-standing films) In this example, the effect of a dispersant on a free-standing film of an electrode mixture was investigated.

[0101] The electrode composite free-standing films obtained in Example 2 (CNT concentrations of 0.50 wt % and 2.4 wt %) were heated in a vacuum at 600°C for about 2 hours to remove the PAA. Figure 22 shows the results of thermogravimetric analysis (TGA) of the electrode composite free-standing films. As shown in Figure 22, the weight loss rate at 650°C obtained by thermogravimetric analysis is almost consistent with the CNT concentration, confirming that the PAA had been removed. It was found that the electrode composite free-standing films from which the PAA had been removed were also able to stand on their own and had sufficient mechanical strength. It is believed that the strength of the electrode composite free-standing film is derived from the network structure of the CNT.

[0102] (Example 5. Evaluation of the effect of the type of active material on the mixed structure of electrode active material and CNT) In this example, the influence of the type of active material on the mixed structure with the electrode active material was examined.

[0103] An electrode mixture was prepared using a particle size (0.05 to 30 μm) and type that are generally used as an electrode active material. 10 g of the CNT dispersion prepared using hexylene glycol in Example 1 was added to a ternary positive electrode material Li(Ni 0.5 Mn 0.3 Co 0.2 )O2(NMC532), Li(Ni 0.8 Mn 0.1 Co 0.1 )O2(NMC811), single crystal Li(Ni 0.9 Mn 0.05 Co 0.05 )O2(single NMC91), Li(Ni 0.8 Co 0.1 Al 0.10.4 g each of 0.4 g of 0.4-100% SiO2 (NCA811), lithium iron phosphate LiFePO4 (LFP), graphite as a negative electrode, lithium titanate (Li2TiO3), Si, and SiO were added and mixed in a mixer to obtain an electrode slurry. Using the method of Example 2, an electrode mixture layer (active material concentration 95 wt%) was formed, and the electrode mixture layer was peeled off from the stainless steel substrate to obtain an electrode mixture free-standing film.

[0104] It was found that the free-standing films obtained by utilizing the CNT network structure of these active materials had sufficient tensile strength and bending resistance.

[0105] FIG. 23 is a surface scanning electron microscope image of an electrode composite film containing NMC532 as active material particles. FIG. 24 is a surface scanning electron microscope image of an electrode composite film containing NMC811 as active material particles. FIG. 25 is a surface scanning electron microscope image of an electrode composite film containing only NMC91 as active material particles. FIG. 26 is a surface scanning electron microscope image of an electrode composite film containing NCA811 as active material particles. FIG. 27 is a surface scanning electron microscope image of an electrode composite film containing LFP as active material particles. FIG. 28 is a surface scanning electron microscope image of an electrode composite film containing SiO as active material particles. FIG. 29 is a surface scanning electron microscope image of an electrode composite film containing Si as active material particles. FIG. 30 is a surface scanning electron microscope image of an electrode composite film containing Li2TiO3 as active material particles. FIG. 31 is a surface scanning electron microscope image of an electrode composite film containing graphite as active material particles.

[0106] As shown in Figs. 23 to 31, in all of these active material particles (size range: 50 nm to 30 µm), CNT network structure parts entangled with the active material particles and dense network structure parts having only CNTs were observed.

[0107] (Example 6. Evaluation of charge / discharge performance of electrode mixture) In this example, the charge / discharge performance of the electrode mixtures prepared in Examples 3 and 5 was evaluated.

[0108] These electrode composites were cut into pieces with a diameter of 1.5 cm, then dried in a vacuum oven at 160°C for 16 hours and used as working electrodes. Lithium metal foil was used as the counter electrode. 1M LiPF6 ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (v / v=1 / 1) solution manufactured by Aldrich was used as the electrolyte. A 2303-type coin cell was fabricated using the electrode composites, and the charge / discharge performance was evaluated.

[0109] Table 4 shows the composition of the positive electrode layer and the battery performance. [Table 4]

[0110] The charge / discharge rate means the current density per initial discharge capacity. The current required to fully charge (or discharge) the battery capacity in 10 hours is defined as 0.1C. As shown in Table 4, all electrode composites showed sufficient capacity density and cycle characteristics even with high-concentration active material of 95.2% by weight or more.

[0111] As described above, by using one embodiment of the present invention, it is possible to produce an electrode mixture film having good charge / discharge characteristics without being limited by the type of active material particles. [Explanation of symbols]

[0112] 10···Secondary battery, 25···Weight average molecular weight, 111···Positive electrode terminal, 121···Negative electrode terminal, 110···Positive electrode, 113···Positive electrode active material layer, 120···Negative electrode, 123···Negative electrode active material layer, 130···Separator, 140···Exterior body, 150···Electrolyte, 1131···Positive electrode active material particle, 1133···Carbon nanotube structure, 1135···Gap, 3000···Magnification, 11331···Carbon nanotube, 11333···Bundle, 11335a···Contact portion, 11335b···Contact portion, 11335c···Contact portion, 11337···Polymer dispersant

Claims

1. a carbon nanotube structure having a plurality of carbon nanotubes, the plurality of carbon nanotubes being entangled to form a network and forming a plurality of gaps in a plane or cross section; a plurality of active material particles disposed in the plurality of gaps, The concentration of the active material particles is 90% by weight or more. Electrode material for secondary batteries.

2. The carbon nanotube structure is a free-standing film. The electrode material for a secondary battery according to claim 1 .

3. In the Raman spectrum of carbon nanotubes, -1 The maximum peak intensity in the range of G, 1310 to 1350 cm -1 When the maximum peak intensity within the range is D, The G / D ratio of the carbon nanotubes is 5 or more and 120 or less. The electrode material for a secondary battery according to claim 1 .

4. The concentration of the carbon nanotubes is 0.1% by weight or more and 10% by weight or less. The electrode material for a secondary battery according to claim 1 .

5. The concentration of the carbon nanotubes is 0.1% by weight or more and 2.5% by weight or less, The concentration of the active material particles is 95% by weight or more. The electrode material for a secondary battery according to claim 1 .

6. The active material particles include any one of a nickel-manganese-cobalt alloy, a nickel-cobalt-aluminum alloy, an olivine-type lithium iron phosphate, a lithium cobalt oxide, a lithium titanate, silicon, a silicon oxide, and graphite; The electrode material for a secondary battery according to claim 1 .

7. The diameter of the active material particles is 50 nm or more and 30 μm or less. The electrode material for a secondary battery according to claim 6 .

8. The carbon nanotube structure further includes a polymer dispersant. The electrode material for a secondary battery according to claim 1 .

9. The carbon nanotubes are single-walled carbon nanotubes. The electrode material for a secondary battery according to claim 1 .

10. The carbon nanotube structure includes a bundle formed from the plurality of carbon nanotubes, The diameter of the bundle is 5 nm or more and 100 nm or less. The electrode material for a secondary battery according to claim 9 .

11. The secondary battery electrode material according to any one of claims 1 to 10, Secondary battery.

12. A solvent; A plurality of active material particles dispersed in the solvent; In the Raman spectrum of carbon nanotubes, -1 The maximum peak intensity in the range of G, 1310 to 1350 cm -1 When the maximum peak intensity within the range is D, A plurality of carbon nanotubes having a G / D ratio of 5 or more and 120 or less and dispersed in the solvent; Including, Slurry for secondary battery electrodes.

13. The active material particles include any one of a nickel-manganese-cobalt alloy, a nickel-cobalt-aluminum alloy, an olivine-type lithium iron phosphate, a lithium cobalt oxide, a lithium titanate, silicon, a silicon oxide, and graphite; The slurry for a secondary battery electrode according to claim 12.

14. The diameter of the active material particles is 50 nm or more and 30 μm or less. The slurry for a secondary battery electrode according to claim 13.

15. Further comprising a polymeric dispersant attached to the carbon nanotubes. The slurry for a secondary battery electrode according to claim 12.

16. The carbon nanotubes are single-walled carbon nanotubes. The slurry for a secondary battery electrode according to claim 12.

17. a bundle formed from the plurality of carbon nanotubes; The diameter of the bundle is 5 nm or more and 20 nm or less. The slurry for a secondary battery electrode according to claim 16.

18. In the Raman spectrum of carbon nanotubes, -1 The maximum peak intensity in the range of G, 1310 to 1350 cm -1 When the maximum peak intensity within the range is D, A dispersion is prepared by adding a plurality of carbon nanotubes having a G / D ratio of 5 or more and 120 or less to a solvent; adding a plurality of active material particles to the dispersion; forming a film of the dispersion liquid containing the plurality of active material particles on a substrate; A method for producing an electrode material for a secondary battery.

19. The carbon nanotubes are single-walled carbon nanotubes. A method for producing the electrode material for a secondary battery according to claim 18.

20. A polymer dispersant is dissolved in the solvent, and the carbon nanotubes are added to the solvent to prepare the dispersion liquid. A method for producing the electrode material for a secondary battery according to claim 18.

Citation Information

Patent Citations

  • Carbon nanotube dispersion liquid for non-aqueous electrolyte secondary battery, resin composition using the same, mixture slurry, electrode film, and non-aqueous electrolyte secondary battery

    JP2021072279A